IMPLEMENTATION OF VACCINATION FOR THE GENERAL COMMUNITY AT THE CAMPUS OF THE HEALTH POLYTECHNIC OF KERTA CENDEKIA - Dimas Hadi Prayoga; Kusuma Wijaya Ridi Putra; Riesmiyatiningdyah Riesmiyatiningdyah; Meli Diana; Dini Prastyo Wijayanti; Agus Sulistyowati; Nina Rizka Rohmawati; Nima Eka Nur Rahmania (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
The public vaccination activity carried out within the Health Polytechnic of Kerta Cendekia is a form of the active role of the academic community of the Health Polytechnic of Kerta Cendekia in dealing with Covid-19 and supports the accelerated vaccination program carried out by the Government of Indonesia. The activity will be held on September 17, 2021, at the Health Polytechnic of Kerta Cendekia Campus. The target of this vaccination activity is the academic community of the Health Polytechnic of Kerta Cendekia and the community around the campus who need vaccines, both the first and second doses. This activity was held in collaboration with the Health Polytechnic of Kerta Cendekia with the Sidoarjo District Health Office. This vaccination activity was attended by 176 people who attended to vaccinate, both the first dose and the second dose. The activity starts at 9.20 WIB and ends at 14.00 WIB. This activity has involved 9 lecturers, 4 staff, and 14 students. In addition, this activity also involved 4 alumni who acted as vaccinators. The activity ran smoothly, in an orderly manner, and still implemented physical distancing in its implementation.